2005
DOI: 10.1158/1055-9965.epi-04-0670
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition of Red Blood Cell Membranes and Risk of Squamous Cell Carcinoma of the Skin

Abstract: Differential effects of fatty acids on carcinogenesis suggest that fatty acid composition is important in tumor development. Arachidonic acid and its metabolites elicit inflammation and promote tumor formation in mouse skin. Inhibitors of the arachidonic cascade inhibit tumor incidence. A population-based case control study in Southeastern Arizona tested the hypothesis that lower levels of arachidonic acid in RBC membranes were associated with decreased risk of skin squamous cell carcinoma (SCC; n = 335 SCC ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 48 publications
6
23
1
Order By: Relevance
“…Although our findings did not show a clear doseresponse relationship, collectively the evidence suggests that moderate omega-3 intake may sustain circulating and target tissue levels to influence early stages of photocarcinogenesis. With respect to omega-6 PUFA, our study failed to confirm earlier findings that higher serum arachidonic acid levels increase SCC risk (11).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although our findings did not show a clear doseresponse relationship, collectively the evidence suggests that moderate omega-3 intake may sustain circulating and target tissue levels to influence early stages of photocarcinogenesis. With respect to omega-6 PUFA, our study failed to confirm earlier findings that higher serum arachidonic acid levels increase SCC risk (11).…”
Section: Discussioncontrasting
confidence: 99%
“…An Arizona-based case-control study showed an inverse association of omega-3 intake and odds of SCC (10), and an increased SCC risk with higher serum levels of arachidonic acid (11). We have also previously reported a marginal increase in SCC risk with greater arachidonic acid intake and a decrease in BCC risk with increasing total omega-6 intake (12).…”
Section: Introductionmentioning
confidence: 70%
“…A large, prospective study in male U.S. health professionals suggested a small but statistically significant positive association between intake of long-chain n-3 fatty acids and risk of basal cell carcinoma, but personal-level past UV exposure could not be accounted for in that study (25). Erythrocyte longchain n-3 fatty acids were not associated with squamous cell carcinoma risk in a case-control study in Arizona, but concentrations of the n-6 fatty acid AA were associated with increased squamous cell carcinoma risk in that study (12). More evidence from studies that are designed to assess specific intake of long-chain fatty acids or biomarkers of these and skin cancer risk is needed.…”
Section: Discussionmentioning
confidence: 74%
“…On the basis of the literature, we had hypothesized that higher concentrations of n-6 fatty acids would be associated with increased p53 immunoreactivity, because p53 immunoreactivity is an early marker of UV-induced carcinogenesis and n-6 fatty acids have been associated with increased tumor growth (10,11) and increased risk of squamous cell carcinoma of the skin (12). However, our results did not suggest such an association; on the contrary they showed that p53 immunoreactivity was lowest in participants with highest total serum n-6 fatty acid concentrations, although the group differences were of borderline statistical significance (P ¼ 0.08).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation